MgF2-Based Luminescing Ceramics; Russian Physics Journal; Vol. 61, iss. 10 - Lisitsyn V. M. Viktor Mikhailovich; Golkovsky M. G. Mikhail Gedalievich; Lisitsyna L. A. Lyudmila Aleksandrovna; Dauletbekova A. K. Alma Kezhemkulovna; Musakhanov D. A. Dosymkhan Abitkhanovich; Vaganov V. A. Vitalii Andreevich; Tulegenova A. T. Aida Tulegenkyzy; Karipbaev Z. T. Zhakyp Tleubaevich (2019, 2019)
Title screen